Investment as a Component of the Financial Mechanism of Foreign Economic Activity Regulation (Economics and region, 2020)
In the paper the necessity of studying investment as a part of the financial mechanism of foreign economic activity regulation is substantiated. The investment is considered as an instrument of this mechanism, within which a set of regulation levers is proposed. The experience of several countries in using the investment regulation is studied, in particular the legal framework for investors admission, the practice of investment promotions and restrictions, investment guarantees. It is shown that in conditions of investment liberalization taking place nowadays, the countries analyzed use the investment levers actively for the development of their foreign economic activity.
Keywords: investments; regulation; foreign economic activity; financial mechanism; regulation levers; investment promotions; investment guarantees